Optimising Basic English: Fun and Interactive Learning for School-Aged Children at St. Andreas Baumata - Rozita Yusniaty Lodo; Polce Aryanto Bessie; Anisia Ivonda Seran; Chamelya V.C Sene; Mansuetus Mola; Antonia Tefa (LKP KARYA PRIMA KURSUS, 2026)
The target beneficiaries comprised 47 school-aged children representing three educational levels. To ensure that instructional activities were developmentally appropriate, participants were divided into three learning groups according to their educational stage. The first group consisted of 21 pupils in Years 1-3 of primary school, the second group included 12 pupils in Years 4-6 of primary school, and the third group comprised 14 lower secondary school students. Fun and interactive learning method were applied. In conducting it, shadowing technique of teaching was implemented at the beginning of teaching class. The results of conducting this teaching service for community at ST. Andreas Baumata are: pupils have basic English such as; how to introduce themselves, telling time, talking about part of body and also telling daily activities.